PENGARUH KEPEMIMPINAN, KOMITMEN ORGANISASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DIMEDIASI KEPUASAN KERJA DAN KOMUNIKASI ORGANISASI (STUDI DI DINAS PERTANIAN DAN KEHUTANAN) KABUPATEN REMBANG - Yenny Eka Kurniawati, 12.5202.0110; Abdul Rozak, Hasan (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to examine and analyze the effect of leadership , organizational commitment and motivation on performance in the mediation of job satisfaction and organizational communication ( the study at the Department of Agriculture and Forestry Rembang ) . The collection of data with a survey method of 96 respondents in the Department of Agriculture and Forestry District Apex. Selection of respondents were conducted by census method . Engineering test data used in this study include the validity test , reliability test , multiple regression analysis , model test , t test and test mediation to test and prove the research hypothesis . Based on the results of the analysis and discussion demonstrate that leadership and motivation positive and significant effect on job satisfaction, organizational communication and performance. While organizational commitment is not positive and significant effect on job satisfaction, organizational communication and performance. The influence of leadership, organizational commitment and motivation more powerful directly on performance than mediation job satisfaction and organizational communication . Keywords : Leadership , Organizational Commitment , Motivation , Job Satisfaction , Organizational Communication , and Performance